Analisis Determinan Tingkat Kepuasan Nasabah Bank Digital Aladin Syariah (Studi Pada Karyawan PT Sumber Alfaria Trijaya Kota Jambi) - Amaluddin Efendi Harahap; Syaparuddin; Candra Mustika (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
This study aims to analyze the influence of religiosity, Islamic financial literacy, perceived ease of use, perceived usefulness, and trust on customer satisfaction among Alfamart employees who use the services of Bank Aladin Syariah. This research employed a quantitative approach using a survey method through questionnaires distributed to 116 respondents selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results of the study indicate that simultaneously religiosity, Islamic financial literacy, perceived ease of use, perceived usefulness, and trust significantly influence customer satisfaction with Bank Aladin Syariah services. Partially, religiosity, perceived usefulness, and trust have a positive and significant effect on customer satisfaction, while Islamic financial literacy and perceived ease of use do not have a significant effect. Trust was found to be the most dominant variable influencing customer satisfaction, as indicated by the largest regression coefficient. The Adjusted R Square value of 72.8% indicates that customer satisfaction can be explained by the independent variables in this study, while the remaining 27.2% is explained by other variables outside the research model. The findings of this study indicate that trust, perceived usefulness, and religiosity play important roles in enhancing customer satisfaction in Islamic digital banking services. Therefore, Bank Aladin Syariah should improve system security, service quality, digital feature innovation, and maintain compliance with Islamic principles in order to increase customer satisfaction